Anti-inflammatory and antithrombotic properties of polar lipid extracts, rich in unsaturated fatty acids, from the Irish marine cyanobacterium Spirulina subsalsa. (July 2022) - Shiels, Katie; Tsoupras, Alexandros; Lordan, Ronan; Zabetakis, Ioannis; Murray, Patrick; Kumar Saha, Sushanta
Graphical abstract: Highlights: Spirulina contains anti-inflammatory and antithrombotic polar lipids (PL) Spirulina PL strongly inhibited platelet activating factor (PAF) and thrombin. SQDG, MGDG and glycosphingolipids were the most bioactive Spirulina glycolipids. The most bioactive phospholipids were PC and PE rich in omega-3 PUFA and oleic acid. Abstract: The characterization of cardio-protective lipid bioactives from cyanobacteria, such as Spirulina spp ., has rarely been investigated. In this study, neutral lipids, glycolipids, and phospholipids of Irish marine cyanobacterium Spirulina subsalsa, were tested for anti-inflammatory and antithrombotic activities in vitro in human platelets. Glycolipids and phospholipids inhibited strongly platelet aggregation induced by platelet-activating factor (PAF) or thrombin, with IC50 (half maximal inhibitory concentration) values ranging ∼60–110 µg of polar lipids. The characterisation of the glycolipids revealed the presence of sulfoquinovosyl diacylglycerols (SQDG), monogalactosylodiglycerides (MGDG) and glycosphingolipids (cerebrosides and ceramides). Phospholipids contained mostly bioactive phosphatidylcholines (PC) and phosphatidylethanolamines (PE) molecules such as, diacyl-PC, diacyl-PE, alkyl-acyl PC, and alkyl-acyl-PE, as well as considerable amounts of phosphatidylglycerols (PG), phosphatidylinositols (PI), phosphatidylserines (PS), and phosphatidic acids (PA). The total presence of such lipid bioactives with cardio-protective properties makes marine Spirulina subsalsa a candidate as a sustainable source for health supplements with cardiovascular health benefits.